(untitled) (Al-Qamar, 2019)
This paper studies Iqbāl,s understandings of the Quran about the structural components of human consciousness. It argues that these are ten components: individuality, self-sufficiency, concept of not getting anything without effort, righteousness, Ego, destiny, concept of life after death, free and responsible personality, forgetfulness, obdurateness. Each part of consciousness has its own more or less effect. The last two components (forgetfulness and obdurateness) affect the first eight in different ways. This consciousness when becomes pure and clean the configuration process of Khudī starts. Its extreme form is where Allah asks man: “what is your will?”